2020
DOI: 10.1093/reseval/rvaa023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of competitive public funding on scientific output: A comparison between China and the EU

Abstract: Public funding is believed to play an important role in the development of science and technology. However, whether public funding and, in particular, competitive funding from public agencies actually helps to increase scientific output (i.e. publications) remains a matter of debate. By analysing a dataset of co-publications between China and the EU and a dataset of joint project collaborations in European Framework Programs for Research and Innovation [FP7 and Horizon 2020 (H2020)], we investigate whether dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The extent to which researchers have responded to the health needs caused by infectious diseases reveals the connections between the "supply side " of science and knowledge and "demand side" in health fields (11). Academic research is a complex, collaborative, and goal-oriented activity (12), driven by diverse individual and social factors (13). At the individual end of the spectrum, we have, for example, the curiosity of the researcher (14).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which researchers have responded to the health needs caused by infectious diseases reveals the connections between the "supply side " of science and knowledge and "demand side" in health fields (11). Academic research is a complex, collaborative, and goal-oriented activity (12), driven by diverse individual and social factors (13). At the individual end of the spectrum, we have, for example, the curiosity of the researcher (14).…”
Section: Introductionmentioning
confidence: 99%
“…Although China was considered as the second largest spender on R&D globally as of 2020 [ 12 ], lack of funding was indicated as the main obstacle for targeted research [ 13 ]. A recent study by Wang et al [ 14 ] reported that the Chinese government funding is mainly associated with enhancement of measurable and recognizable scientific output, whereas EU is more likely to fund projects with social impact, that might not directly be transferable to scientific output [ 15 ]. The experts considered that partnerships between funding organizations, government, pharmaceutical industry and academic institutions have the potential to facilitate funding programs or activities.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, China can introduce and transform a number of foreign advanced agricultural production methods and production technologies, so as to promote the improvement of agricultural Tfpch [34]. The increasing investment in scientific research, especially in agriculture scientific research, also plays an important role in the improvement of agricultural total factor productivity [35]. In terms of the decomposition indexes of agricultural Tfpch, this study finds a trend of enhanced technical change and weakened technical efficiency change, which is worthy of attention.…”
Section: Temporal Variation Patterns Of Total Factor Productivity In ...mentioning
confidence: 99%